William and Mary. - Claydon, Tony (Very interesting people., 2007)
Definitive, concise, and very interesting ... From William Shakespeare to Winston Churchill, the Very Interesting People series provides authoritative bite-sized biographies of Britain's most fascinating historical figures - people whose influence and importance have stood the test of time. Each book in the series is based upon the biographical entry from the world-famous Oxford Dictionary of National Biography. The Very Interesting People series includes the following titles: 1. William Shakespeare by Peter Holland 2. George Eliot by Rosemary Ashton 3. Charles Dickens by Michael Slater 4.